The state as an essential value (Darūriyyāt) of the Maqāṣid al-Sharī‘ah - Kayadibi, Saim (Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2019)
Muslim scholars have mainly considered the maqāṣid al-sharī‘ah within three categories: ḍarūriyyāt (the essentials), ḥājiyyāt (the complementaries) and tahsīniyyāt (the desirables or the embellishments). The concept of maṣlaḥah is meant to protect the maqāṣid al-sharī‘ah (the higher objectives of sharī‘ah), which consist of seven essential values, namely religion, life, intellect, lineage, wealth, honour and state, all of which promote the people’s welfare and prevent all kind of evils. They are considered essentials because neglecting them would cause total social disruption and anarchy. Even though classical scholars considered the darūriyyāt to be six in number, this article suggests that the value of “state” be added to this list. The values in the darūriyyāt category must be upheld and protected from any real or unexpected threats either by maintaining the essentials or removing the disruption. The concept of state is just as essential as the other six values, for without it, all of them would be endangered and considered incomplete. Therefore, the “state” value guarantees the continued existence of other values. In this paper, the author argues that this value should be regarded as a seventh essential value will be elaborated through a “skeleton metaphor”.